2012
DOI: 10.1007/978-1-4614-1897-9
|View full text |Cite
|
Sign up to set email alerts
|

Topological Aspects of Nonsmooth Optimization

Abstract: The goal of this paper is to compare alternative stationarity notions in structured nonsmooth optimization (SNO). Here, nonsmoothness is caused by complementarity, vanishing, orthogonality type, switching, or disjunctive constraints. On one side, we consider geometrically motivated notions of N -, N -, and N -stationarity in terms of Fréchet, Mordukhovich, and Clarke normal cones to the feasible set, respectively. On the other side, we advocate the notion of topologically relevant T-stationarity, which adequat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 64 publications
(127 reference statements)
0
12
1
Order By: Relevance
“…Izmailov [14] studied some kind of semi-continuity and Lipshitz continuity of locally optimal solution mapping under some mild conditions. More recently, Jongen et al [16] and Shikhman [30] studied the stability for C-stationarity and S-stationarity and showed that, under suitable conditions, the C-/S-stationary points are strongly stable in the sense of Kojima [18]. A natural question is "are there any stability results for the M-stationarity?…”
mentioning
confidence: 99%
“…Izmailov [14] studied some kind of semi-continuity and Lipshitz continuity of locally optimal solution mapping under some mild conditions. More recently, Jongen et al [16] and Shikhman [30] studied the stability for C-stationarity and S-stationarity and showed that, under suitable conditions, the C-/S-stationary points are strongly stable in the sense of Kojima [18]. A natural question is "are there any stability results for the M-stationarity?…”
mentioning
confidence: 99%
“…Now, we recall the definitions of C-MFCQ and C-stationarity. Note that C-MFCQ is called MFC in [10,11,17,18,34].…”
Section: Remark 31mentioning
confidence: 99%
“…Note that the set Tx (r ,s,ρ,σ ) is a so-called tangent space, see e.g. [34]. The next result is obvious and therefore its proof is skipped.…”
Section: A Necessary Condition For Strong Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…There are many applications where MPCC is used, we refer e.g. to [23,28]. The results of this paper refer to the particular structure imposed by the complementarity constraints.…”
Section: Introductionmentioning
confidence: 99%